2015
DOI: 10.1002/2015ms000432
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the sensitivity of maximum, limiting, and potential tropical cyclone intensity to SST: Observations versus the FSU/COAPS global climate model

Abstract: Previous research quantified the sensitivity of limiting intensity to SST for observed tropical cyclones (TCs) and for TCs generated by two global climate models (GCMs). On average, a 1 C increase in sea surface temperature (SST) is associated with a 7.9 m s 21 increase in the statistical upper limit of observed intensity. Conversely, a 1 C increase in SST does not significantly affect the limiting intensity of GCM-generated TCs. The study presented here builds on previous research in two ways: (1) A compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 39 publications
(76 reference statements)
1
21
0
Order By: Relevance
“…The FSU-COAPS model successfully simulates the thermodynamic environment needed to sustain intense TCs, but does not actually generate intense TCs. Strazzo et al [2015] speculate that this occurs partly because model grid spacing is too coarse to resolve the inner core and thus the maximum wind speed of simulated TCs. Strazzo et al [2015] also find that the sensitivity of observed maximum TC intensity to SST is not statistically different from the sensitivity of observed potential intensity to SST.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…The FSU-COAPS model successfully simulates the thermodynamic environment needed to sustain intense TCs, but does not actually generate intense TCs. Strazzo et al [2015] speculate that this occurs partly because model grid spacing is too coarse to resolve the inner core and thus the maximum wind speed of simulated TCs. Strazzo et al [2015] also find that the sensitivity of observed maximum TC intensity to SST is not statistically different from the sensitivity of observed potential intensity to SST.…”
Section: Introductionmentioning
confidence: 93%
“…Strazzo et al [2015] speculate that this occurs partly because model grid spacing is too coarse to resolve the inner core and thus the maximum wind speed of simulated TCs. Strazzo et al [2015] also find that the sensitivity of observed maximum TC intensity to SST is not statistically different from the sensitivity of observed potential intensity to SST. If model resolution explains the inability of the FSU-COAPS model to simulate the sensitivity of TC maximum intensity to SST, we might expect that the sensitivity of simulated maximum intensity to SST will approach the sensitivity of simulated potential intensity to SST as model resolution increases.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations